First assessment of the ecological status of Karaoun reservoir, Lebanon. Issue 2 (June 2014) - Fadel, Ali; Lemaire, Bruno J.; Atoui, Ali; Vinçon‐Leite, Brigitte; Amacha, Nabil; Slim, Kamal; Tassin, Bruno
Abstract Many reservoirs have been constructed throughout the world during the 20th century, with many also suffering from eutrophication. The resulting increased phytoplankton biomass in reservoirs impairs their use. Except for Lake Kinneret, the environmental status of lakes and reservoirs in the Middle East is poorly documented. Karaoun reservoir, also known as Qaroun, Qaraoun or Qarun, is the largest water body in Lebanon, having been constructed for irrigation and hydropower production. This present study reviews Karaoun reservoir, including its characteristics, uses, water quality and phytoplankton succession, to assess the environmental status of the reservoir on the basis of the few existing previous publications about the reservoir. Since 2004, which is 39 years after its construction, the reservoir is considered to be hypereutrophic, with low phytoplankton biodiversity and regular blooms of toxic cyanobacteria. The nutrient and trace metal concentrations would not prevent use of the reservoir for a drinking water supply for Beirut, as is currently being planned, although not all the micropollutants in the lake were documented. Karaoun reservoir is compared to other monitored lakes and reservoirs around the Mediterranean Sea. They share annual toxic cyanobacteria blooms of Aphanizomenon ovalisporum and of Microcystis aeruginosa. The phytoplankton composition and succession of Karaoun reservoir is more similar to El Gergal reservoir (Spain) than nearby natural lakes such as Lake Kinneret (Israel) and Lake Trichonis (Greece). Phytoplankton diversity in Karaoun reservoir was the lowest, due to higher nutrient concentrations and a larger decrease in water level in the dry season. Karaoun reservoir represents an interesting example of the potential response of the phytoplankton community in other lakes and reservoirs during the drought periods expected to occur as a result of global climate change.